Comparative analysis of small RNAs released by the filarial nematode Litomosoides sigmodontis in vitro and in vivo. - Juan F Quintana; Sujai Kumar; Alasdair Ivens; Franklin W N Chow; Anna M Hoy; Alison Fulton; Paul Dickinson; Coralie Martin; Matthew Taylor; Simon A Babayan; Amy H Buck (Public Library of Science (PLoS), 2019)
Background The release of small non-coding RNAs (sRNAs) has been reported in parasitic nematodes, trematodes and cestodes of medical and veterinary importance. However, little is known regarding the diversity and composition of sRNAs released by different lifecycle stages and the portion of sRNAs that persist in host tissues during filarial infection. This information is relevant to understanding potential roles of sRNAs in parasite-to-host communication, as well as to inform on the location within the host and time point at which they can be detected. Methodology and principal findings We have used small RNA (sRNA) sequencing analysis to identify sRNAs in replicate samples of the excretory-secretory (ES) products of developmental stages of the filarial nematode Litomosoides sigmodontis in vitro and compare this to the parasite-derived sRNA detected in host tissues. We show that all L. sigmodontis developmental stages release RNAs in vitro, including ribosomal RNA fragments, 5'-derived tRNA fragments (5'-tRFs) and, to a lesser extent, microRNAs (miRNAs). The gravid adult females (gAF) produce the largest diversity and abundance of miRNAs in the ES compared to the adult males or microfilariae. Analysis of sRNAs detected in serum and macrophages from infected animals reveals that parasite miRNAs are preferentially detected in vivo, compared to their low levels in the ES products, and identifies miR-92-3p and miR-71-5p as L. sigmodontis miRNAs that are stably detected in host cells in vivo. Conclusions Our results suggest that gravid adult female worms secrete the largest diversity of extracellular sRNAs compared to adult males or microfilariae. We further show differences in the parasite sRNA biotype distribution detected in vitro versus in vivo. We identify macrophages as one reservoir for parasite sRNA during infection, and confirm the presence of parasite miRNAs and tRNAs in host serum during patent infection.